Investigations on Sound Absorption Properties of Luffa Fibrous Mats. Issue 3 (4th May 2018) - Thilagavathi, G.; Neela Krishnan, S.; Muthukumar, N.; Krishnan, Santhana
ABSTRACT: In this study, the natural fibrous mats were developed using luffa fibrous materials and their sound absorption properties were investigated. Kapok/cotton web was used as middle layer in between two mats in order to improve the sound absorption efficiency. Four fibrous mats with different composition of layers were developed using thermal bonding. The developed mats were tested for Noise Reduction Coefficient (NRC) as perASTM E 1050 . The parameters influencing sound absorption properties of the developed mats such as addition of kapok/cotton web on the mats, thickness of mats and air gap maintained in the impedance tube during testing have been investigated. The sound absorption properties of developed mats improved due to the addition of kapok/cotton web and increased air gap. The increase in thickness of mats resulted in increase in sound absorption properties. Luffa mats having 4 layers had NRC value of 0.39 at the frequency range of 250 Hz to 2000 Hz which is comparable with commercially available glass fiber board.